Menjalani Kehidupan di Tengah Malapetaka: Gempa Kerinci 1909 - Hudaya, Padhil; Setiawati, Nur Aini; Purwanto, Bambang (Department of History, Faculty of Humanities, Diponegoro University, 2023)
This paper discusses the ability of the Kerinci people to adapt during the recovery process after the earthquake catastrophic in June 1909, when they had to deal with massive damage, environmental changes, various internal limitations, inadequate support from external elements, and the impact of colonial political and military annexation. The research utilizes colonial government report documents, written records of eyewitnesses, newspaper reports, and oral traditions. Inspired by the concept of